Piano for dummies - Neely, Blake; Pearl, David (Hoboken Wiley, 2009)
Explains how to become familiar with the keyboard, read music, practice scales, explore different musical styles, and select and maintain an instrument.
Includes bibliographical references, filmography and index.
Keywords: Piano -- Instruction and study; Piano -- Study and teaching